Américo Negrette and Huntington's disease - Mariana Moscovich; Renato P. Munhoz; Nilson Becker; Egberto Reis Barbosa; Alberto J. Espay; Roberto Weiser; Hélio A.G. Teive (Arquivos de Neuro-Psiquiatria, 2011)
The authors present a historical review of the seminal clinical contribution of Professor Américo Negrette, a Venezuelan neurologist, to the evolution of scientific knowledge about Huntington's disease.